2014
DOI: 10.1002/jso.23560
|View full text |Cite
|
Sign up to set email alerts
|

Complications and survival associated with operative procedures in patients with unresectable pancreatic head adenocarcinoma

Abstract: Despite advancements in endoscopic palliation, operative bypasses are still commonplace in patients with unresectable pancreatic head cancer. In this study, patients treated with operative procedures had a high rate of complications without a notable improvement in outcome. These findings highlight the importance of identifying unresectable disease prior to surgery and support a selective approach to palliative operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
(40 reference statements)
5
28
1
Order By: Relevance
“…7,20 To explain the observed increased mortality in older patients undergoing major surgery, several studies have evaluated the impact of postoperative complications on patient survival. 6,20,21 A population based study by Finlayson et al demonstrated higher complication rates in older patients undergoing pancreatic resection for cancer. 8 Likewise, in a retrospective cohort study by Haigh et al using NSQIP data, age > 70 years was found to be an independent prognostic factor for increased postoperative complications following pancreaticoduodenectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,20 To explain the observed increased mortality in older patients undergoing major surgery, several studies have evaluated the impact of postoperative complications on patient survival. 6,20,21 A population based study by Finlayson et al demonstrated higher complication rates in older patients undergoing pancreatic resection for cancer. 8 Likewise, in a retrospective cohort study by Haigh et al using NSQIP data, age > 70 years was found to be an independent prognostic factor for increased postoperative complications following pancreaticoduodenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…46 Two recent, large, population based studies demonstrated that advanced age was independently associated with longer lengths of stay and higher mortality rates following pancreatic surgery. 7,8 Previous studies have focused solely on mortality following pancreatectomy in older patients 7,911 or failure to rescue for all patients undergoing pancreatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, if patients were not symptomatic but had evidence of impending obstruction, only about 40% had a poor outcome. 21 If endoscopic expertise is available, stenting is often preferable for gastric obstructions, although this is heavily dependent on operator ability. Stents for gastric outlet obstruction are noted to be quite successful (approximately 90%) with rare complications.…”
Section: Gastric Outlet Obstructionmentioning
confidence: 99%
“…Surgical biliary decompression had been the mainstay of treatment for biliary decompression in such patients. However, it had significantly high morbidity and mortality in the postoperative period 5–7. Percutaneous transhepatic biliary drainage (PTBD) has a more favorable adverse events profile than surgical decompression but is associated with complications like fistula formation, repeat intervention, recurrent infection, and needs a long-term external catheter drainage, thereby leading to poor quality of life 810.…”
Section: Introductionmentioning
confidence: 99%